Analisis Kesalahan Mahasiswa dalam Menyelesaikan Soal Pembuktian Struktur Aljabar - Suci Yuniati (Beta: Jurnal Tadris Matematika, 2014)
This study was based on the lack of ability of students to solve problems of proving. Students’ low ability can be seen from the works of students in solving problems of algebra structures. They are still experiencing difficulties in linking known information to what will be proven in the matter, although in the meetings, exercises are always raised about the proving. Maybe the problem was caused by students’ difficulty in linking the concepts so they found it difficult to determine the steps to be taken in a matter of proving. Besides the difficulty in linking the existing concepts, there were other mistakes made that caused low outcomes. The writer as the subject lecturer analyzed mistakes in the algebraic structure committed: what were students mistakes in solving problems of proving and what factors cause the student made the mistakes abaut groups? This study used descriptive qualitative research method. Data collection methods were test and interview. The data obtained described what would be analyzed. The research subjects in this study were students of semester VI Mathematics Education Department of the State Islamic University of Sultan Syarif Kasim Riau (UIN Suska Riau) Academic Year 2011/2012. There was only one class who took the course in algebraic structures, that was class VI C, amount 50 students. From the mistakes writer identified: 1) mistakes in receiving the information, 2) mistakes associated with the concept of, 3) mistakes in calculating and 4) mistakes associated with the material prerequisites. It appeared that a lot of mistakes made, the writer got a picture of the students’ performance and hence the writer should improve the learning process to lessen the mistakes occurred.